1978
DOI: 10.1207/s15328023top0503_12
|View full text |Cite
|
Sign up to set email alerts
|

The Questionable Status of Student Evaluations of Teaching

Abstract: Until much more research is done, caution should be exercised in possible misuse of these ratings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

1980
1980
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 16 publications
0
18
0
1
Order By: Relevance
“…What appears clear is that considerably more research is needed on student course evaluations if they are to have significant impact upon the livelihood of universityfaculty and if faculty are to rely on them for self-improvement. In fact, this study adds to the evidence which suggests that the sole use of student ratings to evaluate teaching effectiveness is questionable (Greenwood, et al, 1976;Chandler, 1978).…”
Section: <001mentioning
confidence: 84%
See 1 more Smart Citation
“…What appears clear is that considerably more research is needed on student course evaluations if they are to have significant impact upon the livelihood of universityfaculty and if faculty are to rely on them for self-improvement. In fact, this study adds to the evidence which suggests that the sole use of student ratings to evaluate teaching effectiveness is questionable (Greenwood, et al, 1976;Chandler, 1978).…”
Section: <001mentioning
confidence: 84%
“…In the past, student ratings were collected at the discretion of the individual instructor and were utilized primarily for self improvement (Centra, 1976). More recently, many colleges and universities require the administration of these rating forms, and the results often are important factors in faculty promotion, tenure and salary decisions (Bejar, 1975;Chandler, 1978;Seldin & Wakin, 1974). Thus, there are two practical reasons (teacher improvement and personnel decisions) for careful study of the construction of rating forms andvarious factors that may affect thedatathoseforms yield.…”
mentioning
confidence: 99%
“…Faculty members generally believe that student evaluations are biased by a number of factors they believe to be unrelated to teaching effectiveness. These include course difficulty, grading leniency, instructor popularity, student interest in subject before course, and student's GPA Chandler 1978;Sheehan 1975). Although most studies have concluded that there is no basis for concern about these potential biases Sackloss 1973;Garverick and Carter 1962), a few studies have revealed that class workload or difficulty were the variables most likely to be strongly correlated with students' evaluations of teaching (Pohlman 1975).…”
Section: Effectivenessmentioning
confidence: 99%
“…Other professionals (Chandler, 1978;Tetenbaum, 1975) are not as sanguine. They are impressed by the overwhelming finding that the student ratings depend primarily on the personality and popularity of the professor when teaching.…”
Section: Professional Attitudes Towards Student Ratings Of Professorsmentioning
confidence: 99%